Improved Efficiency of Ultraviolet B Light‐Emitting Diodes with Optimized p‐Side. Issue 20 (9th September 2020) - Kolbe, Tim; Knauer, Arne; Rass, Jens; Cho, Hyun Kyong; Mogilatenko, Anna; Hagedorn, Sylvia; Lobo Ploch, Neysha; Einfeldt, Sven; Weyers, Markus
Abstract : The effects of design and thicknesses of different optically transparent p‐current spreading layers [short‐period superlattice, superlattice (SL), and bulk p‐ Al 0.38 Ga 0.62 N ] as well as the type and thickness of the p‐GaN cap layer on the electrical and optical characteristics of 310 nm ultraviolet light‐emitting diodes (LEDs) are investigated. Scanning transmission electron microscopy measurements display self‐organized composition variations in the nonpseudomorphically grown SLs, reducing the effect of increased hole injection efficiency of a SL. In addition, the effect leads to an increased operation voltage. In contrast, the bulk p‐AlGaN layer has a uniform composition and the corresponding LEDs show only a slightly lower output power along with a lower operating voltage. If the thickness of the p‐AlGaN bulk layer in the LED is reduced from 150 nm to 50 nm, the output power increases and the operating voltage decreases. Finally, LEDs with a nonuniform p + ‐GaN cap layer from a 3D island‐like growth mode feature the highest output power and operating voltage. In contrast, the output power and operating voltage of LEDs with a smooth and closed cap depend on the thickness of p + ‐GaN. The highest output power and lowest operating voltage are achieved for LEDs with the thinnest p + ‐GaN cap. Abstract : The design and thicknesses of different optically transparent p‐current spreading layers as well as the type and thickness of p‐GaN cap layer on the electrical and optical characteristics of 310 nm ultraviolet light‐emitting diodes (LEDs) are investigated. The highest output power and lowest operating voltage are achieved for LEDs with the thinnest p‐AlGaN current spreading layer and thinnest p + ‐GaN cap.